Trends in life expectancy and age-specific mortality in England and Wales, 1970-2016, in comparison with a set of 22 high-income countries: an analysis of vital statistics data - David A Leon, ProfPhD; Dmitry A Jdanov, PhD; Vladimir M Shkolnikov, PhD (Elsevier, 2019)
Summary: Background: Since 2010, the rate of improvement in life expectancy in the UK has slowed. We aimed to put this trend in the context of changes over the long term and in relation to a group of other high-income countries. Methods: We compared sex-specific trends in life expectancy since 1970 and age-specific mortality in England and Wales with median values for 22 high-income countries (in western Europe, Australia, Canada, New Zealand, Japan, and the USA). We used annual mortality data (1970-2016) from the Human Mortality Database. Findings: Until 2011-16, male life expectancy in England and Wales followed the median life expectancy of the comparator group. By contrast, female life expectancy was below the median and is among the lowest of the countries considered. In 2011-16, the rate of improvement in life expectancy slowed sharply for both sexes in England and Wales, and slowed more moderately in the comparator group because of negative trends in all adult age groups. This deceleration resulted in a widening gap between England and Wales and the comparators from 2011 onwards. Since the mid-2000s, for the first time, mortality rates in England and Wales among people aged 25-50 years were appreciably higher than in the comparator group. Interpretation: Although many countries have seen slower increases in life expectancy since 2011, trends in England and Wales are among the worst. The poor performance of female life expectancy over the long-term is in part driven by the relative timing of the smoking epidemic across countries. The previously overlooked higher mortality among young working-age adults in England and Wales relative to other countries deserves urgent attention. Funding: None.